المخلفات الورقية و إمكانيات أستغلالها اقتصاديًا (Comprehensive Journal of Science, 2025)
The researcher studied paper waste and its potential economic exploitation. Recycling paper waste is of significant environmental and economic importance because it contributes to reducing the depletion of natural resources such as energy, water, and forests, which are vital to global climate stability.The increased demand for paper has increased the number of paper mills and their types in the world, and our Arab nation has kept pace with the development and prosperity of this industry due to the increasing and urgent need for paper. Large and diverse factories have been established in various countries of the Arab world for the production and manufacture of pulp and forming factories.Despite the care and attention given by most Arab governments to paper waste factories, the paper production industry remains small and simple compared to global production.Despite these available investment opportunities, there are obstacles in this regard, the most important of which are the financing problems for these projects, especially in light of the difficult economic conditions facing Arab countries, the recurring crises, and the lack of expertise and skilled labor in this industry. The study also pointed to some successful international experiences in this field..